Strategic imperatives of institutional development of organic market - Bezus, Roman; Безус, Роман Миколайович; Bilotkach, Ihor; Білоткач, Ігор Анатолійович; Kurbatska, Larysa; Курбацька, Лариса Миколаївна; Koberniuk, Serhiy; Кобернюк, Сергій Олександрович; Kadyrus, Iryna; Кадирус, Ірина Григорівна (Transilvania University of Brasov, 2019)
The paper studied the institutional development of organic products market in Ukraine. The relevance of the study of the development of Ukrainian organic agricultural market is explained with the necessity to create the preconditions for economic strategies in agriculture and strengthening the competitiveness of domestic producers both on a national and world markets. The aim of the article is to make a definitive analysis of the institutional imperatives of the economic development and the definition of institutional factors in effective mechanism of production, distribution, and consumption of organic agricultural products. The concept of the institutional imperatives of the organic agricultural market's development was determined. Conducted study allowed to conclude that the strategic imperatives of the Ukrainian organic market development are concentrated both in the sphere of the regulation mechanism of organic agro-industrial production and in the production of organic agricultural products. У статті досліджено інституційний розвиток ринку органічної продукції в Україні. Актуальність дослідження розвитку українського ринку сільського господарства пояснюється необхідністю створення передумов для економічних стратегій сільського господарства та посилення конкурентоспроможності вітчизняних виробників як на національному, так і на світовому ринках. Метою статті є остаточний аналіз інституціональних імперативів економічного розвитку та визначення інституціональних факторів ефективного механізму виробництва, розподілу та споживання органічної сільськогосподарської продукції. Визначено інституціональні імперативи розвитку ринку органічного сільського господарства. Проведене дослідження дозволило зробити висновок, що стратегічні імперативи розвитку органічного ринку України зосереджені як у сфері механізму регулювання органічного агропромислового виробництва, так і у виробництві органічної сільськогосподарської продукції.
Стратегічні імперативи інституційного розвитку органічного ринку
Keywords: institutional development; інституційний розвиток; imperatives; імперативи; organic farming; органічне землеробство; organic products market; органічний ринок продукції